2020
DOI: 10.1002/celc.202000811
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Nanoplating of Iridium: Template‐Assisted Nanotube Deposition for the Continuous Flow Reduction of 4‐Nitrophenol

Abstract: Electroless plating is a powerful tool in nanofabrication and is available for many of the noble transition metals. There is, however, a striking lack of electroless plating procedures for the rarer platinum‐group metals. In this work, two plating baths for nanoscale iridium coatings are developed and their conformality and nanofabrication potential are showcased by coating ion‐track‐etched polycarbonate membranes, creating Ir nanotubes in the process. Both plating solutions yield morphologically different dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 89 publications
(162 reference statements)
0
17
1
Order By: Relevance
“…Nowadays, TeMs are used as filtration membranes for water purification [ 20 , 21 ] or effective adsorbents and are commercially available. Combining the inherent advantages of TeMs and metal nanostructures provides composite membranes that are excellent candidates in a variety of promising material science applications, such as biotechnology [ 22 , 23 ], catalysis [ 24 , 25 , 26 , 27 , 28 ], medicine [ 29 , 30 ], sensors [ 21 , 31 ], and radiation resistive and magnetic materials [ 32 , 33 ]. In our previous study, we created Cu/CuO in the nanochannels and surface of poly(ethylene terephthalate) (PET) TeMs by electroless template-assisted deposition of copper and subsequent low-temperature annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, TeMs are used as filtration membranes for water purification [ 20 , 21 ] or effective adsorbents and are commercially available. Combining the inherent advantages of TeMs and metal nanostructures provides composite membranes that are excellent candidates in a variety of promising material science applications, such as biotechnology [ 22 , 23 ], catalysis [ 24 , 25 , 26 , 27 , 28 ], medicine [ 29 , 30 ], sensors [ 21 , 31 ], and radiation resistive and magnetic materials [ 32 , 33 ]. In our previous study, we created Cu/CuO in the nanochannels and surface of poly(ethylene terephthalate) (PET) TeMs by electroless template-assisted deposition of copper and subsequent low-temperature annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…[9], [10] Recently, we showed that nanoscale electroless Ir plating is possible as long as the choice of metal precursor, complexing agent and reducing agent is carefully considered. [7] In this case, either citrate or ethylene diamine (EDA) proved to be suitable stabilizers, when NaBH4 is used as reducer. Figure 1a shows SEM images of Ircoated ion-track etched polycarbonate membranes, prepared using a citrate stabilized plating bath.…”
Section: Synthesis: Electroless Ir Platingmentioning
confidence: 99%
“…XPS and XRD measurements on a similar deposit have confirmed that metallic Ir is deposited predominantly. [7] However, small amounts of surface oxides are to be expected, due to the comparatively high oxygen affinity of Ir. Interestingly, the presence of both Ir and IrOx has been linked to an increased catalytic activity of the material.…”
Section: Synthesis: Electroless Ir Platingmentioning
confidence: 99%
See 2 more Smart Citations